Birds, butterflies and flowers in the tropics are not more colourful than those at higher latitudes - Rhiannon L. Dalrymple; Darrell J. Kemp; Habacuc Flores‐Moreno; Shawn W. Laffan; Thomas E. White; Frank A. Hemmings; Marianne L. Tindall; Angela T. Moles (Global Ecology and Biogeography, 2015)
Aim The idea that species are generally more colourful at tropical latitudes has held great appeal among biologists since the days of exploration by early naturalists. However, advances in colour quantification and analysis only now allow an objective test of this idea. We provide the first quantitative analysis of the latitudinal gradient in colour on a broad scale using data from both animals and plants, encompassing both human‐visible and ultraviolet colours. Location A ustralia. Methods We collected spectral reflectance data from 570 species or subspecies of birds, adult forms of 424 species or subspecies of butterflies and the flowers of 339 species of plants, from latitudes ranging from tropical forests and savannas at 9.25° S , to temperate forests and heathlands at 43.75° S . Colour patch saturation, maximum contrast between patches, colour diversity and hue disparity between patches were calculated for all species. Latitudinal gradients in colour were analysed using both regression analyses and comparisons of categorically temperate and tropical regions. We also provide phylogenetically independent contrast analyses. Results The analyses which compared the colour traits of communities and the phylogenetically independent contrasts both show that species in the tropics are not more colourful than those at higher latitudes. Rather, the cross‐species analyses indicate that species further away from the equator possess a greater diversity of colours, and their colours are more contrasting and more saturated than those seen in tropical species. These results remain consistent regardless of whether the mean or the maximum of coloration indices are considered. Main conclusions We demonstrate that birds, butterflies and flowers display similar gradients of colourfulness across latitudes, indicating strong ecological and evolutionary cohesion. However, our data do not support the idea that tropical latitudes contain the most colourful species or house the more colourful biological communities.